IPOB SIT-AT-HOME ORDER AND INSECURITY IN THE SOUTHEAST NIGERIA - Nnodim, Chukwunyere Emmanuel; Osita-Njoku, Agnes; Onyekwere, Iwundu Anthony (African Journal of Social and Behavioural Sciences, 2024)
In recent years, the Southeast region of Nigeria has been plagued by insecurity. This has been attributed to various factors, including the Indigenous People of Biafra (IPOB) sit-at-home order, which has exacerbated tensions in the region. This order, aimed at protesting against perceived discrimination and marginalization, has resulted in widespread disruption of daily activities leading to heightened insecurity in the region. This study therefore examined the effect of the IPOB sit-at-home order on the security situation in southeast Nigeria. The Marxist revolutionary theory was adopted as the study theoretical framework. The study utilized a cross-sectional survey research design. The sample size of the study was 969 which included men, women, youths, business owners, school administrators, government security agents and members of IPOB in southeast Nigeria. Structured questionnaire and Key Person Interview (KPI) were the data collection instruments. Data analysis was processed using Statistical Package for Social Sciences (SPSS) version 20 and analysed using descriptive and inferential statistics, while the content analysis method was adopted for qualitative data. It was found that IPOB sit-at-home order has to a considerable extent increased insecurity in southeast Nigeria. It was also found that increase in attacks on security personnel and fears in the minds of the people were more prominent during the sit-at-home order. Therefore, it was concluded that since IPOB sit-at-home order induced insecurity in southeast Nigeria, to reduce insecurity in the region, government, especially at the Federal level should initiate constructive dialogue with IPOB hierarchies on ways to reach a middle ground, chart a course for peace and reduce insecurity in the region.